PERAN PENYULUHAN TERHADAP PETANI KARET POLA SWADAYA DI KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Alfian Fitrianto; Rosnita '; Roza Yulida (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The research wasaimedto analyze the role of extension on independent smallholder rubberfarmer who included education, dissemination of information or innovation, facilitation, consultation, supervision, and monitoring or evaluation. The research was conducted in GunungToar village of GunungToar district KuantanSingingi Regency from March to December 2015. This research was using survey method. Determination of the respondents is purposive sampling with the consideration that the farmer is following the activities of the extension and is include into the group of farmers. The Samples of this research was taking as many 120 farmers by the total were 60 from Toar and 60 from Gunung Villages. The Data analyzed was used Scale Likert’s Summated Rating (SLR).The results showed that the role of extension on independent smallholder rubber farmer categorized “quite a role” at farming activities in GunungToar District of KuantanSingingi Regency. The extension has categorized “quite a role” in providing consultation, education, dissemination of information or innovation and facilitation, but the extension less instrumental for providing supervision and monitoring or evaluation. The extension is expected to further enhance its role especially in the supervision and monitoring or evaluation is still categorized less of the role. Keyword: The role of extension, independent smallholder rubber farmer